ANALYSIS OF THE LEBAK BULUS MRT TOD AREA, DKI JAKARTA, BASED ON CHALLENGES AND EXPECTATIONS OF CONVENIENCE ORIENTATION - Zul Setiawan (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
Transit-oriented development (TOD) is often defined in terms of mixed development that is close to and/or oriented toward mass transit facilities. General characteristics of TOD include urban cohesiveness, pedestrian and bicycle friendly, public spaces near stations, and stations designed to be community centers. The Lebak Bulus area is strategic and is quite popular as a terminal area that has the potential to support transportation between regions and between cities, as well as being a gathering point for community groups from various levels and backgrounds. In principle, the change in function of the terminal area to the TOD area is expected to have a positive impact on the behavior of public transportation users, although there are still some things that need to be improved. As a recommendation from this study, it is necessary to improve accessibility, such as by improving road and sidewalk conditions, as well as improving feeder transportation and parking services for private vehicle users. In addition, it is necessary to rearrange the environment around the station by optimizing the potential of buildings around the station, improving the quality of parks, pedestrians, and crossing areas, and considering the use of renewable energy. Increased security and safety (use of CCTV) also need attention. The implication of this research is that the TOD area must be built by taking into account the aspects of sustainability, the role of the community and stakeholders (government, developers, and the community) in the development of the TOD area is very important. By implementing the recommendations and implications of this research, it is hoped that the Lebak Bulus MRT TOD area of DKI Jakarta can develop optimally and provide maximum benefits for the community. Keywords: Transit Oriented Development, TOD, Lebak Bulus MRT, convenience